2018
DOI: 10.1002/hep4.1159
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumoral effects of exercise on hepatocellular carcinoma growth

Abstract: Regular physical exercise has many beneficial effects, including antitumor properties, and is associated with a reduced risk of developing hepatocellular carcinoma (HCC). Less is known about the impact of exercise on HCC growth and progression. Here, we investigated the effects of exercise on HCC progression and assessed whether any beneficial effects would be evident under sorafenib treatment and could be mimicked by metformin. American Cancer Institute rats with orthotopic syngeneic HCC derived from Morris H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…Hepatocellular carcinoma (HCC), a malignant tumor that occurs from liver cells, is the most common primary liver cancer, which is a serious hazard to human health and is one of the few cancers with rising incidence in recent decades [1,2]. Radiotherapy is effective in the treatment of many malignant tumors, but HCC is resistant to radiation [3][4][5], and a strategy to increase its radiation sensitivity is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC), a malignant tumor that occurs from liver cells, is the most common primary liver cancer, which is a serious hazard to human health and is one of the few cancers with rising incidence in recent decades [1,2]. Radiotherapy is effective in the treatment of many malignant tumors, but HCC is resistant to radiation [3][4][5], and a strategy to increase its radiation sensitivity is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Our work complements the small number of studies that have evaluated the positive effect of lifestyle interventions on the histological features of NASH [18][19][20]. In addition, our study confirms in yet another model that exercise not only arrests the development of liver tumors [13] but attenuates progression [14]. Furthermore, we have reinforced the notion that the benefit of exercise in suppressing tumors is sustained in NAFLD well after sinusoidal capillarization, ER stress, apoptotic processes, and evidence of mitochondrial dysfunction are established.…”
Section: Resultssupporting
confidence: 79%
“…For instance, regular physical activity significantly decreases the occurrence of tumors, from 100% down to 70%, in a model of NASH induced by the ablation of hepatocellular PTEN [13]. We also confirmed that the exercise-related mechanism was the activation of AMPK and inhibition of the mTOR/S6K pathway [13,14,37]. This mechanism holds for the current model of dietary-induced NASH.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Even when drugs to treat non-alcoholic steatohepatitis will be available, lifestyle changes will remain an essential component of the therapeutic plan of these patients. In the last years, a strong association between lifestyle and hepatocellular carcinoma (HCC) has become evident (2)(3)(4). In patients with NAFLD, the annual incidence of HCC is 0.44 per 1,000 person/year and almost 50% of cases develops in a non-cirrhotic liver resulting in a diagnosis at an advanced stage with a worse prognosis (1,5).…”
mentioning
confidence: 99%